Many-objective particle swarm optimisation algorithm based on multi-elite opposition mutation mechanism in the internet of things environment. (15th May 2023) - Kang, Lanlan; Liu, Naiwei; Cao, Wenliang; Chen, Yeh-Cheng
Multi-objective optimisation problem in Internet of Things technology has been widely concerned by researchers. The family of multi-objective particle swarm optimisation is among the most representative ones. However, there still exist the shortcomings of overspending and premature convergence. This paper proposes a many-objective particle swarm optimisation algorithm based on opposition-based mutation for elite mechanism. The new algorithm mainly includes three strategies: (1) Opposition-based learning population initialisation strategy, which is designed to avoid the blindness and uncertainty of initial population, and improves the distribution of population and accelerates speed of exploration. (2) Multi-elite opposition mutation mechanism, which is proposed to help particles get away from local optimal positions via a targeted exploration in the search space. (3) Singularity archive technique, which is established to disturb the global evolution trend and further balance the contradiction of convergence and diversity of the population. The effectiveness of the proposed algorithm is verified by comparing 11 algorithms in the simulation experiments.